2014
DOI: 10.1128/jvi.01107-14
|View full text |Cite
|
Sign up to set email alerts
|

The Matrix Gene Segment Destabilizes the Acid and Thermal Stability of the Hemagglutinin of Pandemic Live Attenuated Influenza Virus Vaccines

Abstract: The threat of future influenza pandemics and their potential for rapid spread, morbidity, and mortality has led to the development of pandemic vaccines. We generated seven reassortant pandemic live attenuated influenza vaccines (pLAIVs) with the hemagglutinin (HA) and neuraminidase (NA) genes derived from animal influenza viruses on the backbone of the six internal protein gene segments of the temperature sensitive, cold-adapted (ca) A/Ann Arbor/60 (H2N2) virus (AA/60 ca) of the licensed seasonal LAIV. The pLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 80 publications
3
32
0
Order By: Relevance
“…As previously reported, CA/09 virus fuses at pH 5.2 to 5.5 ( Fig. 2B) (27,28), while VN/1203 and WSN viruses fuse at pH 5.9 to 6.0 ( Fig. 2B) (29), suggesting that in Raw264.7 macrophages, CA/09 would not encounter an optimal acidic environment with a pH of 5.0 to 5.5 until the lysosomal compartment, where the virus can encounter activated proteases that degrade the virus.…”
supporting
confidence: 52%
“…As previously reported, CA/09 virus fuses at pH 5.2 to 5.5 ( Fig. 2B) (27,28), while VN/1203 and WSN viruses fuse at pH 5.9 to 6.0 ( Fig. 2B) (29), suggesting that in Raw264.7 macrophages, CA/09 would not encounter an optimal acidic environment with a pH of 5.0 to 5.5 until the lysosomal compartment, where the virus can encounter activated proteases that degrade the virus.…”
supporting
confidence: 52%
“…The data presented here provide direct evidence that M2 can also protect HA from conformational changes in human H1N1 strains that lack the polybasic cleavage motif. Recently, O'Donnell et al reported that M2 function affects the acid and heat stability of HA proteins of some pandemic strains, including (H1N1)pdm09 (70), but the mechanism was not directly demonstrated. Although M2 enhancement of MX HA function is less pronounced than that of an acid-sensitive H7 HA (9-11), our data with two different H1N1 HA proteins indicate that M2 may promote infection by viruses with non-H7 subtype HA in a strain-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The M gene encodes both the M1 matrix protein and the M2 ion channel. The HA destabilizing property of the M gene in the live attenuated vaccine backbone A/Ann Arbor/60 (H2N2) has been linked to M2 ion channel activity (36), which is required to prevent HA inactivation during trafficking in the mildly acidic secretory pathway (19). The M1 matrix protein contributes to virus assembly, budding, and morphology (37), which may also affect transmissibility (38).…”
Section: Discussionmentioning
confidence: 99%